2021
DOI: 10.1094/phyto-09-20-0412-rvw
|View full text |Cite
|
Sign up to set email alerts
|

Population Genomics of Bacterial Plant Pathogens

Abstract: Population genomics is transforming our understanding of pathogen biology and evolution, and contributing to the prevention and management of disease in diverse crops. We provide an overview of key methods in bacterial population genomics and describe recent work focusing on three topics of critical importance to plant pathology: (i) resolving pathogen origins and transmission pathways during outbreak events, (ii) identifying the genetic basis of host specificity and virulence, and (iii) understanding how path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…In the same study, the authors demonstrated that PAVs from the pan-genome analysis of 10 P. ananatis strains separated the pathogenic strains from the non-pathogenic strains, which was not observed when the core genome was used. Phylogenetic studies conducted so far in P. ananatis have relied only on PAVs, which are mainly horizontally acquired ( Welch et al, 2002 ) contrary to the vertically inherited SNPs ( Straub et al, 2021 ). In the current study, we therefore conducted a comparative phylogenetic study using core genome SNPs, PAVs and wgMLST approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the same study, the authors demonstrated that PAVs from the pan-genome analysis of 10 P. ananatis strains separated the pathogenic strains from the non-pathogenic strains, which was not observed when the core genome was used. Phylogenetic studies conducted so far in P. ananatis have relied only on PAVs, which are mainly horizontally acquired ( Welch et al, 2002 ) contrary to the vertically inherited SNPs ( Straub et al, 2021 ). In the current study, we therefore conducted a comparative phylogenetic study using core genome SNPs, PAVs and wgMLST approach.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we therefore conducted a comparative phylogenetic study using core genome SNPs, PAVs and wgMLST approach. Core SNPs are relied to infer phylogeny as they represent the vertically inherited portion of the genome in the population ( Didelot and Wilson, 2015 ; Straub et al, 2021 ). It was however observed that pathogenic strains clustered together with the non-pathogenic strains (in some groups in the phylogenetic tree) based on core SNPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the number of input genomes may have a role to play and core genes-based phylogeny could probably change if the number of strains/genomes is further increased. It could also be possible that the core genome is impacted by HGT or homologous recombination and, as a result, the phylogenetic relationship based on core genes is obscured or distorted [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, number of input genomes may have a role to play and probably core genes-based phylogeny could change if the number of strains/genomes are further added. It could also be possible that core genome is impacted by HGT or homologous recombination and as a result phylogenetic relationship based on core genes is obscured or distorted [34].…”
Section: An Open Pan-genome Of Pantoea Stewartii Subsp Indologenesmentioning
confidence: 99%